Meta-analysis of genome-wide association studies of aggressive and chronic periodontitis identifies two novel risk loci. (January 2019) - Munz, Matthias; Richter, Gesa; Loos, Bruno; Jepsen, Søren; Divaris, Kimon; Offenbacher, Steven; Teumer, Alexander; Holtfreter, Birte; Kocher, Thomas; Bruckmann, Corinna; Jockel-Schneider, Yvonne; Graetz, Christian; et al.
Abstract Periodontitis is one of the most common inflammatory diseases, with a prevalence of 11% worldwide for the severe forms and an estimated heritability of 50%. It is classified into the widespread moderate form chronic periodontitis (CP) and the rare early-onset and severe phenotype aggressive periodontitis (AgP). These different disease manifestations are thought to share risk alleles and predisposing environmental factors. To obtain novel insights into the shared genetic etiology and the underlying molecular mechanisms of both forms, we performed a two step-wise meta-analysis approach using genome-wide association studies of both phenotypes. Genotypes from imputed genome-wide association studies (GWAS) of AgP and CP comprising 5, 095 cases and 9, 908 controls of North-West European genetic background were included. Two loci were associated with periodontitis at a genome-wide significance level. They located within the pseudogeneMTND1P5 on chromosome 8 (rs16870060-G, P  = 3.69 × 10−9, OR = 1.36, 95% CI = [1.23–1.51]) and intronic of the long intergenic non-coding RNA LOC107984137 on chromosome 16, downstream of the geneSHISA9 (rs729876-T, P  = 9.77 × 10−9, OR = 1.24, 95% CI = [1.15–1.34]). This study identified novel risk loci of periodontitis, adding to the genetic basis of AgP and CP.